Learn to sign the fun way! : let your fingers do the talking with games, puzzles, and activities in American Sign Language - Warner, Penny (Three Rivers Press, 2001)
A guide to learning American Sign Language, describing and illustrating the manual alphabet, as well as signs for numbers, people, animals, food and drink, clothing, colors, sports, feelings, and other subjects, and including a selection of sign language games and activities.